2009
DOI: 10.1038/jid.2009.151
|View full text |Cite
|
Sign up to set email alerts
|

Imiquimod Enhances IFN-γ Production and Effector Function of T Cells Infiltrating Human Squamous Cell Carcinomas of the Skin

Abstract: Squamous cell carcinomas (SCC) are sun-induced skin cancers that are particularly numerous and aggressive in patients taking T cell immunosuppressant medications. Imiquimod is a topical immune response modifier and TLR7 agonist that induces the immunologic destruction of SCC and other skin cancers. TLR7 activation by imiquimod has pleiotropic effects on innate immune cells but its effects on T cells remain largely uncharacterized. Because tumor destruction and formation of immunologic memory are ultimately T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 43 publications
0
77
0
3
Order By: Relevance
“…In contrast, treatment with IFN-γ (100 units/mL) induced increased surface expression of β 2 -microglobulin as well as HLA-A,B,C molecules at least by 2-fold (assessed by measuring mean fluorescence intensity by flow cytometry; data not shown). Alternatively, treatment with imiquimod may induce changes in the microenvironment other than upregulation of MHC-I molecules that support local tumor-specific CD8 + T cells, as has been reported for SCC (5,34). Because the CD8 + T cells of imiquimod-treated BCC patients remain in the peritumoral region and do not seem to penetrate the BCC nests (Fig.…”
Section: No Spontaneous Humoral Immune Responses To Ct Antigens In Nmmentioning
confidence: 86%
“…In contrast, treatment with IFN-γ (100 units/mL) induced increased surface expression of β 2 -microglobulin as well as HLA-A,B,C molecules at least by 2-fold (assessed by measuring mean fluorescence intensity by flow cytometry; data not shown). Alternatively, treatment with imiquimod may induce changes in the microenvironment other than upregulation of MHC-I molecules that support local tumor-specific CD8 + T cells, as has been reported for SCC (5,34). Because the CD8 + T cells of imiquimod-treated BCC patients remain in the peritumoral region and do not seem to penetrate the BCC nests (Fig.…”
Section: No Spontaneous Humoral Immune Responses To Ct Antigens In Nmmentioning
confidence: 86%
“…Recently, it was shown that Aldara treatment resulted in pDC-mediated tumour killing in a murine melanoma model 7 . We and others previously showed that treatment with IMQ and Aldara resulted in upregulation of MHC class I on tumour cells, recruitment of T cells into the tumour, enhancement of their effector function and mobilization of Langerhans cells and inflammatory DCs, as well as in interleukin (IL)-17 production by dermal gd-T cells 8,[9][10][11][12] .…”
mentioning
confidence: 99%
“…For example imiquimod, man-made ligand for TLR7, was shown to inhibit growth of skin carcinoma when applied as an ointment [12,13]. The positive effect of imiquimod was found to be immunologically mediated, because it was due up-regulation of effector function of T cells [14].…”
Section: Introductionmentioning
confidence: 99%